Aquaponics System as an Agricultural Innovation to Provide Alternative Protein Sources on Marginal Land - Yanis, Muhammad Nazarul (Indonesian Journal of Advanced Research, 2025)
The objective of the research program in the MAN Nuruzh Zholam area, Seruyan Regency, Central Kalimantan, is to introduce aquaponic cultivation technology, provide alternative protein, utilize yard land more productively and beautiful, and support economic needs. The methods used in this program include socialization and training in fish and vegetable cultivation (aquaponic system). The stages of this program's activities include socialization about aquaponics, fish, and vegetable cultivation training, implementation of mentoring, monitoring, and evaluation. Community mentoring through this activity also serves as a form of support for the Government's program to optimize beautiful yard land as a sustainable food source, increase its availability, accessibility, and utilization, and increase community income.